2022
DOI: 10.3389/fbioe.2022.1092916
|View full text |Cite
|
Sign up to set email alerts
|

The progress in titanium alloys used as biomedical implants: From the view of reactive oxygen species

Abstract: Titanium and Titanium alloys are widely used as biomedical implants in oral and maxillofacial surgery, due to superior mechanical properties and biocompatibility. In specific clinical populations such as the elderly, diabetics and patients with metabolic diseases, the failure rate of medical metal implants is increased significantly, putting them at increased risk of revision surgery. Many studies show that the content of reactive oxygen species (ROS) in the microenvironment of bone tissue surrounding implant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 195 publications
0
15
0
1
Order By: Relevance
“…497 Some studies reported rates of 10% to 20% of implant failures in diabetic patients versus the normal rate between 1% and 3% in the normal population. 498 In contrast, other reviews found no differences in the implant failure rates between diabetic patients and healthy patients. 499,500 Even when long-term studies report no survival differences, a delayed healing process and higher marginal bone loss have also been observed.…”
Section: Metabolicsyndromementioning
confidence: 95%
“…497 Some studies reported rates of 10% to 20% of implant failures in diabetic patients versus the normal rate between 1% and 3% in the normal population. 498 In contrast, other reviews found no differences in the implant failure rates between diabetic patients and healthy patients. 499,500 Even when long-term studies report no survival differences, a delayed healing process and higher marginal bone loss have also been observed.…”
Section: Metabolicsyndromementioning
confidence: 95%
“…This antibacterial characteristic is especially valuable for implants such as cardiovascular devices, where infections pose serious risks to patient health. 238,239 Integrating TiN into biomedical implants represents a significant advancement in the field. By leveraging TiN's unique properties, medical devices can provide safer, more reliable, and longer-lasting patient solutions.…”
Section: Biomedical Implantsmentioning
confidence: 99%
“…However, their overproduction can lead to oxidative stress, potentially compromising the biocompatibility of the implant and causing tissue damage. 12,13 Nanoceria (Ce) emerges as a remarkable candidate due to its unique ability to modulate ROS levels. As a potent ROS scavenger, Ce offers a promising avenue for mitigating oxidative stress and fostering a favorable environment for STI.…”
Section: Introductionmentioning
confidence: 99%
“…These different coating strategies have been studied to improve the antibacterial properties, osteogenic ability, and interaction with the gingival tissue of Ti implants. , Reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ), are essential cellular signaling molecules. However, their overproduction can lead to oxidative stress, potentially compromising the biocompatibility of the implant and causing tissue damage. , Nanoceria (Ce) emerges as a remarkable candidate due to its unique ability to modulate ROS levels. As a potent ROS scavenger, Ce offers a promising avenue for mitigating oxidative stress and fostering a favorable environment for STI. , …”
Section: Introductionmentioning
confidence: 99%